ENSS (Expanded Nursing Stress Assessment) version 1,0: An Android-Based Mobile Application Efficient Stress Assessment in Nurses - Lena Atoy; Dewi Sartiya Rini; Rusna Tahir; Dewi Nurviana Suharto (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2024)
The nursing profession is a profession that is prone to experiencing stress. Long work duration in accompanying patients is one of the factors that causes stress in nurses. To anticipate work-related stress problems, it is necessary to periodically identify the level of stress experienced by nurses. The use of mobile applications needs to be developed for easy and efficient stress assessment Android-based which are expected to help nurses identify the stress they are experiencing. The aim of this study was to developing a stress assessment application android-based to identify stress levels efficiently and effectively. This research uses design Research and Development (R&D) with a product development and validation approach through use trials on 34 nurses with a sampling method that is the total sample. Test use using the instrument System Usability Scale (SUS). The research developed an Android-based stress analysis application called ENSS version 1.0 with login features, stress questionnaire main menu and load interpretation. The test was tested by respondents with a score of 74.78 in the category of Acceptable or Admissible. The ENSS application has been developed and is suitable for use in the identification of stress levels in nurses. The application of ENSS is an assessment of the stress level of nursing so that proper management can be carried out.